A New Polygenic Model for Nonfamilial Colorectal Cancer Inheritance Based on the Genetic Architecture of the Azoxymethane-Induced Mouse Model. Issue 3 (1st March 2020) - Bissahoyo, Anika C; Xie, Yuying; Yang, Lynda; Pearsall, R Scott; Lee, Daekee; Elliott, Rosemary W; Demant, Peter; McMillan, Leonard; Pardo-Manuel de Villena, Fernando; Angel, Joe M; Threadgill, David W
Abstract: The azoxymethane carcinogen model of non-familial colorectal cancer has been used in mice to identify six new susceptibility loci and confirm 18 of 24 previous detected susceptibility loci. Using a population-based approach, the genetic architecture of colon cancer... The azoxymethane model of colorectal cancer (CRC) was used to gain insights into the genetic heterogeneity of nonfamilial CRC. We observed significant differences in susceptibility parameters across 40 mouse inbred strains, with 6 new and 18 of 24 previously identified mouse CRC modifier alleles detected using genome-wide association analysis. Tumor incidence varied in F1 as well as intercrosses and backcrosses between resistant and susceptible strains. Analysis of inheritance patterns indicates that resistance to CRC development is inherited as a dominant characteristic genome-wide, and that susceptibility appears to occur in individuals lacking a large-effect, or sufficient numbers of small-effect, polygenic resistance alleles. Our results suggest a new polygenic model for inheritance of nonfamilial CRC, and that genetic studies in humans aimed at identifying individuals with elevated susceptibility should be pursued through the lens of absence of dominant resistance alleles rather than for the presence of susceptibility alleles.